X-ray microtomography of mortars exposed to freezing-thawing action - Promentilla, Michael Angelo B. (Animo Repository, 2010)
This paper presents our findings on the application of X-ray microtomography to characterize the internal structure of mortars that were exposed to freezing-thawing action. A microfocus X-ray CT (micro-CT) scanner was used for the nondestructive 3D imaging of internal air voids or cracks at a spatial resolution of the order of 10 microns. Four different types of mortar specimens (i.e., non-air-entrained and air-entrained Portland cement mortar, and non-air-entrained and air-entrained fly ash mortar) were scanned after being subjected to different numbers of freeze-thaw cycles. Coupled with image analysis, the void space obtained from micro-CT was characterized in three dimensions (3D) in terms of void fraction and air void size distribution, as well as, the crack width and tortuosity of the connected crack network. Results suggest that the initial air voids follow a lognormal distribution with the highest population of modal size around 30-50 μm, irrespective of the type of mortar. As the distributed air voids of non-air entrained mortars were relatively few in numbers, the fly ash mortar in particular was the least resistant against frost damage as shown by the formation of internal cracks that meander around the weaker paste-aggregate interface. Indications also suggest that these cracks are well connected and anisotropic in 3D. Copyright © 2010 Japan Concrete Institute.